Venous cerebral thrombosis in children with protein S deficiency: Case report (Research, Society and Development, 2025)
Purpose: Report a case of cerebral venous thrombosis associated with hemorrhage in the region corresponding to the basal ganglia due to protein S deficiency. Case Description: Patient presented with headache associated with projectile vomiting and diarrhea, progressing to altered level of consciousness and right-sided motor deficit. Imaging exams showed abnormalities that led to hospitalization for heparinization and intensive care monitoring. Conclusions: Cerebral venous thrombosis is a rare disease with an estimated incidence of 1.32 per 100,000 people, and it can be triggered by genetic factors, such as protein S deficiency, found in 1.5 to 7% of thrombophilic patients.